(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a multidisciplinary intervention model in the treatment of children with autism spectrum disorder (ASD) at Da Nang City Rehabilitation Hospital. Methods: This non-controlled clinical intervention study used a pre–post design in 79 children aged 16 months to 5 years diagnosed with ASD according to DSM-5 criteria. The interventions included speech therapy, occupational therapy, clinical psychology, physical therapy, special education, and family involvement, with a minimum of 20 hours per week for 6 months. Outcomes were assessed using the Childhood Autism Rating Scale (CARS) and the Autism Treatment Evaluation Checklist (ATEC) before and after intervention. Results: After six months, 73.4% of participants achieved at least minimal clinical improvement. The proportion of children classified with severe ASD decreased from 22.8% to 3.8% (p < 0.05). The mean CARS score decreased from 33.9 ± 4.9 to 30.3 ± 3.0, and the mean ATEC score decreased from 84.2 to 60.0 (p < 0.05). All ATEC subscales improved, with the most significant changes in social functioning and language–communication. Conclusion: The multidisciplinary intervention model produced significant improvements in behavior, language, and social functioning among children with ASD. This model represents a comprehensive, feasible, and context-appropriate approach for hospital-based rehabilitation.